Prisma guidelines for systematic and scoping reviews: cultural mapping of creative industries - Santos, Luana (2022)
While policymakers have had a great interest in debating Cultural and Creative Industries (CCIs), there is a lack of literature presenting a systematic overview of existing relevant research regarding CCIs mapping. This paper discusses and compares PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines for Systematic Review (SR) and PRISMA for Scoping Review (ScR) for synthesizing research on CCIs mapping. ‘A systematic review attempts to collate all empirical evidence that fits pre-specified eligibility criteria to answer a specific research question. It uses explicit, systematic methods that are selected to minimize bias, thus providing reliable findings from which conclusions can be drawn and decisions made’ (Liberati et al. 2009: 65). ScR ‘(…) follow a systematic approach to map evidence on a topic and identify main concepts, theories, sources, and knowledge gaps’ (Tricco et al. 2018: 467). After analyzing and applying the guidelines and further documentation on both protocols, the ScR revealed to be more suitable in a complex field with distinct terminologies, production contexts, methodologies and objectives. Since certain topics in SR become optional, ScR is easier to apply in fields in which methods are difficult to compare and quantify, such as the Arts and Humanities.